New Testament conjectural emendation in the nineteenth century : Jan Hendrik Holwerda as a pioneer of method - Kamphuis, Bart L. F. (New Testament Tools, Studies and Documents, 2018)
In New Testament Conjectural Emendation in the Nineteenth Century Bart L.F. Kamphuis investigates the life and work of Jan Hendrik Holwerda (1805-1886), who should be seen as the father of the Dutch Movement of Conjectural Criticism. Through a close study of his correspondence, Kamphuis reconstructs Holwerda's remarkable scholarly biography. He then positions his text-critical theory against the views of Lachmann, Tischendorf and Tregelles. Finally, Holwerda's corpus of New Testament conjectures is analysed by means of a newly proposed classification, while specific conjectures are discussed in the context of the history of scholarship on the passages concerned. This study not only significantly contributes to our understanding of the history of New Testament textual criticism, but also shows that several of Holwerda's conjectures have lasting relevance.